Synthesis and biological activity of glycosyl-1H-1,2,3-triazoles - Slámová, Kristýna; Marhol, Petr; Bezouška, Karel; Lindkvist, Lise; Hansen, Signe G; Křen, Vladimír; Jensen, Henrik H (Bioorganic & medicinal chemistry letters, 2010)
Glycosyl 1,2,3-triazoles with alpha-D-gluco, beta-D-gluco, alpha-D-galacto, beta-D-galacto and beta-2-acetamido-2-deoxygluco (GlcNAc) stereochemistry were prepared by reaction of the corresponding azides with vinyl acetate under microwave irradiation. The deprotected glucosyl and galactosyl triazoles did not display inhibitory activity against the tested glycosidases at 1 mM. Of the four fungal glycosidases evaluated, GlcNAc-triazole was found to be hydrolyzed by Talaromyces flavus CCF 2686 beta-N-acetylhexosaminidase. Beta-GlcNAc-triazole was furthermore established to act as a strong ligand of rat and human natural killer cell activating receptors.
Keywords: Animals; lidé; hydrolýza; Triazoles; triazoly; Humans; Hydrolysis; krysa rodu Rattus; zvířata; Rats